Entrepreneurship Improvement Training in Palembang City - Muhammad Iqbal; Sherly Malini; Agung Indariansyah (Universitas 45 Surabaya, 2023)
This community service aims to provide skills and knowledge to women entrepreneurs who work on batik fabrics in weaving centers in the city of Palembang. service This approach uses interviews, observation, field studies and field practice. The results of this service are related to non- formal education-based women's empowerment, there are several processes ranging from awareness raising to increasing women's interest in being involved in empowerment, the awareness process is carried out by identifying needs that are used as the basis decision making, the next program is to encourage and invite women to participate in the program by outreach to the wider community, the process of transforming knowledge and skills is carried out by training in an effort to provide knowledge and skills for women that are adapted to the conditions of women and carried out by the method of withdrawing batik materials that are the goal is an effort to increase women's independence in the development of batik as well as efforts to improve the quality of batik production that is able to compete in the national market and international.